2012
DOI: 10.1021/am201645g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of EDTA-Graphene Oxide for Pb (II) Removal

Abstract: Chelating groups are successfully linked to graphene oxide (GO) surfaces through a silanization reaction between N-(trimethoxysilylpropyl) ethylenediamine triacetic acid (EDTA-silane) and hydroxyl groups on GO surface. EDTA-GO was found to be an ideal adsorbent for Pb(II) removal with a higher adsorption capacity. EDTA-modification enhances the adsorption capacity of GO because of the chelating ability of ethylene diamine triacetic acid. This study investigates the adsorption and desorption behaviors of heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
396
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 775 publications
(421 citation statements)
references
References 73 publications
16
396
1
8
Order By: Relevance
“…Meidanchi and Akhavan (2014) Table 11 shows absorption capacity of different heavy metals on GO MMM. Madadrang et al (2012) linked the chelating groups to graphine oxide surfaces via a silanization reaction between N-(trimethoxysilylpropyl) ethylenediamine triacetic acid (EDTA-silane) and hydroxyl groups on GO surface. The adsorption capacity for Pb(II) removal was found to be 479 ± 46 mg/g at pH 6.8.…”
Section: Graphene Oxide-water Treatmentmentioning
confidence: 99%
“…Meidanchi and Akhavan (2014) Table 11 shows absorption capacity of different heavy metals on GO MMM. Madadrang et al (2012) linked the chelating groups to graphine oxide surfaces via a silanization reaction between N-(trimethoxysilylpropyl) ethylenediamine triacetic acid (EDTA-silane) and hydroxyl groups on GO surface. The adsorption capacity for Pb(II) removal was found to be 479 ± 46 mg/g at pH 6.8.…”
Section: Graphene Oxide-water Treatmentmentioning
confidence: 99%
“…20 mg/L Pb(II) and 20 mg/L Cu(II) working solutions were prepared from the 1000 mg/L stock solutions. HNO 3 and NaOH were used to adjust pH of Pb(II) and Cu(II) working solutions to 6 ± 0.5 and 5 ± 0.5, respectively [3,22]. In the batch experiments, 0.5 g of Zn-BTC was added to Pb(II) and the Cu(II) working solutions separately.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…Cu 3 (BTC) 2 -SO 3 H also exhibited high Cd(II) uptake capacity, thus has a potential use for cadmium removal [19]. Other type of MOFs previously used in heavy metals absorption studies were Graphene Oxides (GO) [4], [6], EDTA-Graphene Oxide (EDTA-GO) [3], [20] for Pb(II) removal and MOF-5 [16] and Graphene Oxides-CdS [21] for Cu(II) removal. However, an optimum experimental conditions to maximize heavy metals absorption efficiency of MOFs were not well studied.…”
mentioning
confidence: 99%
“…Madarang and co-workers have shown that using a EDTA-GO composite material the Pb(II) adsorption capacity is higher than for GO or EDTA-rGO. 48 This is due to the additional binding sites available for the Pb(II) contaminant when both GO and EDTA are present in the composite material.…”
Section: Water Remediation By Adsorptionmentioning
confidence: 99%